Wybory samorządowe a Internet na przykładzie gminy Słubice. - Domańska, Martyna (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2020)
The article presents, how different actors use the Internet in the local elections in the municipality of Slubice. The research clearly show that despite the obstacles, the candidate willingly used the network to promote himself. Local media inform about the election. They were also used by candidates to promote his candidature. For local and state government Internet was an additional place to provide information to voters.